DOMESTICATION OF INTERNATIONAL STRATEGIES IN TOBACCO CONTROL: THE CASE OF SOUTH AFRICA - Charles Ngwena (Obiter, 2022)
With an estimated 1.2 billion smokers in the world, tobacco use is of pandemic proportions. The relationship between tobacco use, and death and disease is well established. It is not only active, but also passive or secondary smoking that is injurious to health. The morbidity and mortality from tobacco rivals that of HIV/AIDS. According to the World Health Organisation (WHO), tobacco and AIDS have become the two leading global causes of premature death. Smoking causes an estimated 4 million deaths per year (World Health Organisation). Unless checked, tobacco-related mortality is projected to rise phenomenally to 10 million by the year 2030, with the preponderance of the mortality (about 7 million deaths) occurring in developing countries. In the last twenty years or so, there has been a reversal in smoking trends between the developed world and the developing world. In the developed world, smoking has decreased. In the developing world, smoking has increased, with women and children constituting the most vulnerable group. There is little doubt that the developing world has been targeted by the tobacco industry for exploitation in tobacco use, in part to make up for lost profits in the developed world. The reasons for the increase in smoking prevalence are, however, composite. In part, the increase in prevalence is an outcome of vulnerability to aggressive advertising and sponsorship by the tobacco industry. In part it is also an outcome of poor knowledge about the risks associated with smoking, poor health promotion infrastructure, absent or weak tobacco control activism, poor government funding for tobacco control, and lack of political will to control tobacco products on the part of government. There is consensus among health experts that tobacco-related diseases are the single most preventable cause of death and disease, and that measures must be taken to control tobacco use. Moreover, there is international consensus on the use of law and other coercive measures as instruments for controlling tobacco use. This article seeks to explore and evaluate the extent to which South Africa has responded to the challenge of controlling tobacco use. It is submitted that though the efficacy of the South African strategies has yet to be tangibly demonstrated in terms of translating into positive health gains, South Africa has made substantial progress in implementing international tobacco control norms. The Tobacco Products Control Act of 1999 is significant evidence in this regard.